2024
DOI: 10.3390/met14050509
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Johnson-Cook Constitutive and Damage-Fracture Model Parameters of a Q345C Steel

Fengquan Hu,
Xin Liu,
Boshi Wang
et al.

Abstract: Due to the rapid development of high-speed trains, the service safety of vehicle body materials and structures has become a focal point in transport and impact engineering. Numerical simulations on the collision resistance of vehicle materials and structures are crucial for the safety assessment and optimal structural design of high-speed trains but have not been fully investigated due to the lack of damage model parameters. This study focuses on the Johnson-Cook (J-C) constitutive and damage-fracture models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The modified JC and the JC models were employed to predict Al7075 behavior at increased temperatures; however, modified JC models have better predictions due to adjustments in the temperature term [31]. Fengquan Hu et al [32] investigated the JC constitutive and failure-fracture model parameters for Q345C steel. Levgen et al [33] identified the material parameters at elevated strain-rates using ballistic impact tests and performed inverse finite element analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The modified JC and the JC models were employed to predict Al7075 behavior at increased temperatures; however, modified JC models have better predictions due to adjustments in the temperature term [31]. Fengquan Hu et al [32] investigated the JC constitutive and failure-fracture model parameters for Q345C steel. Levgen et al [33] identified the material parameters at elevated strain-rates using ballistic impact tests and performed inverse finite element analysis.…”
Section: Introductionmentioning
confidence: 99%